2022
DOI: 10.1155/2022/8366665
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Rubber-Reinforced Halloysite Nanotubes/Carbon Black Hybrid Fillers for Oil Seal Applications: Thermal Stability and Dynamic Mechanical Properties

Abstract: In this study, we show that adding halloysite nanotubes (HNT) to carbon black (CB)-packed acrylic rubber (ACM) composites improves their thermal properties. The thermo-oxidative stability, thermal stability, and dynamic mechanical properties of ACM composites (filled simply with 70 phr CB) and ACM hybrid composites comprising a fixed amount of CB (60 phr) and a variable amount of halloysite nanotubes (HNT) (2, 4, 6, 8, and 10 phr) were investigated. As evidenced by the oxidation induction time analysis, hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In order to produce thermally stable materials, the grafting of polymers' backbones with polymers exhibiting better thermal stability, the use of high-temperature polymer as a matrix, or the incorporation of a heat-resistant filler into the polymer are often used. In recent years, nano-sized fillers have been researched for the development of polymeric materials [11]. Studies have shown that nano-composites containing nano-fillers in very low concentrations (1-8 phr) have much better thermal stability than standard products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to produce thermally stable materials, the grafting of polymers' backbones with polymers exhibiting better thermal stability, the use of high-temperature polymer as a matrix, or the incorporation of a heat-resistant filler into the polymer are often used. In recent years, nano-sized fillers have been researched for the development of polymeric materials [11]. Studies have shown that nano-composites containing nano-fillers in very low concentrations (1-8 phr) have much better thermal stability than standard products.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that nano-composites containing nano-fillers in very low concentrations (1-8 phr) have much better thermal stability than standard products. Layered silicates, graphene, and carbon nanotubes are popular research topics of many scientific studies [11][12][13][14]. Ho and co-workers have shown that the use of modified montmorillonite or carbon nanofibers as fillers in thermoplastic polyurethane elastomers (TPU) significantly reduces the flammability of the final products.…”
Section: Introductionmentioning
confidence: 99%